A meta-analysis of family accommodation and OCD symptom severity. (April 2016) - Wu, Monica S.; McGuire, Joseph F.; Martino, Charitie; Phares, Vicky; Selles, Robert R.; Storch, Eric A.
Abstract: Family accommodation in obsessive–compulsive disorder (OCD) is characterized by myriad behaviors, such as modifying family routines, facilitating avoidance, and engaging in compulsions to reduce obsessional distress. It has been linked to various deleterious outcomes including increased functional impairment and poorer treatment response for OCD. Although extant literature suggests a linear relationship between family accommodation and OCD symptom severity, the magnitude and statistical significance of this association has been inconsistent across studies, indicating that moderators may be influencing this relationship. The present study examined this relationship using meta-analytic techniques, and investigated sample-dependent (age, gender, comorbid anxiety/mood disorders) and methodological (administration method and number of items used in family accommodation measure, informant type, sample size, publication year) moderators. Forty-one studies were included in the present meta-analysis, and the overall effect size (ES) for the correlation between family accommodation and OCD symptom severity was moderate ( r = .42). Moderator analyses revealed that the number of items on the family accommodation scale moderated the ES. No other sample-dependent or methodological characteristics emerged as moderators. In addition to being the first systematic examination of family accommodation moderators, these results highlight the moderate relationship between family accommodation and OCD severity that is influenced by measurement scales. Findings may be used to guide clinical care and inform future investigations by providing a more nuanced understanding of family accommodation in OCD. Highlights: This meta-analysis synthesized an overall effect size (ES) across 41 studies. The ES for family accommodation and OCD symptom severity was r = .42. This is the first meta-analysis to examine purported moderators of this ES. The number of items used in the family accommodation measures moderated the ES. Despite adequate power, no sample-dependent variables significantly moderated the ES.